1999
DOI: 10.1055/s-2007-978713
|View full text |Cite
|
Sign up to set email alerts
|

IGF-II in Primary Human Colorectal Tumors: Peptide Level, Activated Promoters, Parental Imprinting and Gene Rearrangement

Abstract: IGF-II is a polypeptide growth factor with growth and differentiation promoting activities, involved in human development. We have reported previously IGF-II mRNA and peptide overexpression in primary human colon cancers. Here we show that the IGF-II peptide content is increased in six primary colon cancers compared to the corresponding healthy tissues. The IGF-II transcripts in healthy and cancerous colon tissues were identified by Northern blotting and RT-PCR. Promoters P3 and P4 were active in most tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Therefore, diet and associated factors may influence the risk of colorectal cancers [155], and circulating IGF-I levels may regulate colon cancer growth and metastasis [156]. IGF-II mRNA and IGF-II peptide are also overexpressed in primary human colon cancers [157]. The levels of circulating IGF-II are likewise elevated in patients with colorectal adenomas and colorectal cancer [158].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Therefore, diet and associated factors may influence the risk of colorectal cancers [155], and circulating IGF-I levels may regulate colon cancer growth and metastasis [156]. IGF-II mRNA and IGF-II peptide are also overexpressed in primary human colon cancers [157]. The levels of circulating IGF-II are likewise elevated in patients with colorectal adenomas and colorectal cancer [158].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Additionally, human hepatocellular carcinoma and colon carcinoma derived cell lines were shown to express IGF-II transcripts from P3 and P4, respectively (Schneid et al 1993). When comparing primary colon cancers to corresponding healthy tissue, Winkler et al (1999) found that IGF-II was overexpressed, and that the transcripts were derived from P3 and P4. When ovarian tumors were analyzed, transcripts from P3 and P4 were found to be more frequent and abundant than transcripts from P1 and P2; further high levels of expression from P3 and P4 were associated with signiWcantly increased risks of death (Lu et al 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-II is the single most overexpressed gene in colorectal cancer relative to normal colonic epithelial cells and elevated circulating levels of IGF-II is associated with the development of colorectal cancer [16,17]. In addition, the IGF-IR is overexpressed in colorectal cancer compared to normal tissues [6].…”
Section: Discussionmentioning
confidence: 99%